From 'Fetish' to 'Aura': The Charisma of Objects? - Radermacher, Martin (Journal of religion in Europe, 2019)
In the history of religions, material artifacts have often played an important role as mediations of the sacred.' They were and are worshipped, venerated, and sometimes destroyed for their assumed supernatural powers. The article reviews theoretical concepts that engage with the charismatic capacities of objects (fetish,' cultic image,' and aura') and discusses literature about charismatic objects.' It deals with the question of what kind of charisma objects may have and suggests that the term charisma,' when defined in a specific way, is a useful concept to describe and compare specific material objects from different religious traditions. These conceptual and methodological considerations are illustrated by a brief discussion of Christian relic veneration.